Pengaruh Kredibilitas Beauty Vlogger Terhadap Keputusan Pembelian Produk Kosmetik “S” - Vira Tri Handriana; Mari Okatini Armandari; Neneng Siti Silfi Ambarwati (Populer: Jurnal Penelitian Mahasiswa, 2023)
With the development of using social media in gaining more information, a cosmetic product potential buyer will search for more information from various sources, including reviews from beauty vloggers on YouTube. Beauty Vlogger existence can be a form of information exchange that can affect the sales of a product. Miss “X” becomes one of beauty vlogger in Indonesia who also makes review of cosmetic brand, including cosmetic brand “S”. Purpose of this research is to find out how much a beauty vlogger’s credibility can affect the decision purchasing of “S” cosmetic products. This research used Trustworthiness, Expertise, and Attractiveness as independent variables. The research methodology used in this research was a quantitative method that calculated by SMARTPLS 3.0. The population of this research was the subscribers of Miss “X”’s YouTube channel. In collecting data, the writer used non probability sampling with some criterions. The study sample of this research was 100. The result of the study shows that beauty vlogger Miss “X”’s credibility affects the purchasing decision of “S” cosmetic products by 33,8%. Trustworthiness has a positive and significant effect towards Purchasing Decision. However, Expertise and Attractiveness do not have significant effect towards “S” cosmetic products despite being positive.